EFEKTIVITAS MEDIA BLOK PECAHAN DALAM MENINGKATKAN PEMAHAMAN KONSEP PECAHAN PADA SISWA SEKOLAH DASAR: ANALISIS BERDASARKAN GENDER - Silvia; Nila Kesumawati; Eka Fitri Puspa Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low ability of students to understand fraction concepts due to the use of conventional learning methods that do not involve concrete media. This research uses a quantitative experimental method with a posttest-only control group design. The population of the study was all students of SD Negeri 92 Palembang totaling 294 students, and the sample consisted of two classes IV, namely class IV A with 20 students as the control class and class IV B with 19 students as the experimental class. The data collection technique was carried out through a written post-test based on indicators of mathematical concept understanding abilities. Data were analyzed using a two-way ANOVA test. The results of the study showed that: (1) there is a significant effect of fraction block media on students' mathematical concept understanding abilities. (2) there is no significant difference in the average ability to understand mathematical concepts based on gender. (3) there is no difference in the effect of fraction block media on students' conceptual understanding abilities when viewed from gender